Response of pearlmillet to hydrogel application and zinc fertilization under semi-arid conditions of Rajasthan: Hydrogel and Zn response on pearl millet - Reema; Dudwal, B L; Dhayal, B C; Choudhary, Anisha; Choudhary, Jitendra (Annals of Arid Zone, 2023)
A field experiment was conducted at Agronomy farm, S.K.N. College of Agriculture, Jobner (Rajasthan) during the kharif season of 2021 on loamy sand soil. The experiment was laid out in factorial randomized block design comprised 16 combinations of treatment viz., four levels of hydrogel (control, 2.5 kg ha-1, 5.0 kg ha-1 and 7.5 kg ha-1) and four levels of zinc fertilization (control, foliar spray of ZnSO4 @ 0.25 %, 0.5 % and 0.75 %).The pearlmillet crop under the influence of pusa hydrogel @ 5.0 kg ha-1, being at par with pusa hydrogel 7.5 kg ha-1 significantly increased earhead length, earhead girth, grain weight per earhead and 1000 grains weight over pusa hydrogel 2.5 kg ha-1 and the control. Results showed that foliar spray of ZnSO4 0.5 % significantly improved growth parameters viz., plant height, dry matter accumulation at successive growth stages, number of tillers and yield attributes viz., earhead length, earhead girth, grain weight per earhead and 1000 grains weight thereby grain, stover and biological yield of pearlmillet crop over foliar spray of ZnSO4 0.25 % and control and was found at par with foliar spray of ZnSO4 0.75 %. Thus, the application of pusa hydrogel (5.0 kg ha-1) and foliar application of ZnSO4 (0.5 %) together in pearlmillet crop was found productive.